1994
DOI: 10.1080/01140671.1994.9513818
|View full text |Cite
|
Sign up to set email alerts
|

Fungicide resistance in populations of cucurbit powdery mildew (Sphaerotheca fuliginea)

Abstract: Cucurbit powdery mildew samples from Australian cucurbit production areas were assessed for their sensitivity to fungicides. Resistance to benzimidazoles was highest (44%) followed by resistance to demethylation inhibitors (39%), organophosphates (21%), and hydroxypyrimidines (13%). Many collections were resistant to more than one fungicide group. Populations from rockmelon crops were more often resistant than those from less intensively managed pumpkin crops. There were also differences in the spectra of resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 6 publications
1
14
0
Order By: Relevance
“…From Bangladesh, Bakr (2007) reported that Tilt 250 EC (0.05%), Thiovit (0.2%), and Bordeaux mixture (1%) were effective to control powdery mildew disease of jujube. Similar findings have also been reported by other investigators (Bent, 1978;O'Brien et al, 1988;O'Brien, 1994;Singh et al, 1995;Cheah and Page 1997). Yadav et al (1980) and Singh and Sidhu (1985) found that Carbendazim (0.2%) can control powdery mildew disease.…”
Section: Cost and Returnsupporting
confidence: 91%
“…From Bangladesh, Bakr (2007) reported that Tilt 250 EC (0.05%), Thiovit (0.2%), and Bordeaux mixture (1%) were effective to control powdery mildew disease of jujube. Similar findings have also been reported by other investigators (Bent, 1978;O'Brien et al, 1988;O'Brien, 1994;Singh et al, 1995;Cheah and Page 1997). Yadav et al (1980) and Singh and Sidhu (1985) found that Carbendazim (0.2%) can control powdery mildew disease.…”
Section: Cost and Returnsupporting
confidence: 91%
“…Unfortunately, the authors do not have accurate data on fungicide use and applications that can support the differences observed in resistance frequencies in terms of a differential use of fungicides in the different locations. High resistance levels detected in Almeria, especially in zucchini and melon isolates, can probably be attributed to higher selection pressure in these crops, highly sensitive to powdery mildew, where fungicide sprays are more frequently applied 33. In Murcia the geographical proximity to Almería could be responsible for the relatively high resistance observed in this area, although genetic diversity studies are yet to be performed to test this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…However, some resistant strains have been able to persist in the absence of selection pressure from fungicide use. Benzimidazole-resistant strains have persisted for many years after use was discontinued (9,93). In addition, this tactic is unlikely to be implemented if the target fungicide is highly effective for controlling other diseases on the same crop, as is the case with azoxystrobin, which, in addition to powdery mildew, also controls anthracnose, belly rot, downy mildew, gummy stem blight, and leaf spots caused by Alternaria and Cercospora.…”
Section: Challenges and Future Outlookmentioning
confidence: 99%
“…Because strains have been detected with resistance to as many as four classes of fungicides, it is clear that the cucurbit powdery mildew fungus is capable of thwarting a complex fungicide program (19,93,125).…”
Section: Challenges and Future Outlookmentioning
confidence: 99%